The moderating role of perceived health risks on the acceptance of genetically modified food - Cabelkova, Inna; Sanova, Petra; Hlavacek, Martin; Broz, David; Smutka, Lubos; Prochazka, Petr (Frontiers in Public Health, 2024)
The public perspective on genetically modified foods (GMFs) has been intensely debated and scrutinized. Often, discussions surrounding GMF tend to revolve solely around the potential health risks associated with their consumption. However, it is essential to acknowledge that public perceptions of genetically modified foods are multifaceted, encompassing environmental concerns, ethical considerations, and economic implications. This paper studies the factors predicting GMF acceptance employing the representative sample of the Czech population (N = 884, aged 18–90 years, M ± SD: 48.17 ± 17.72; 53.40% women, 18.04% with higher education). The research relies on the Behavioral Change Model and the Health Belief Model. We employ hierarchical ordinal regressions to study the effects of information, environmental concerns, perceived health risks, food habits, purchasing habits, and socio-demographics on GMF acceptance. The results suggest that the (un)willingness to purchase GMF is primarily driven by the health risks - the environmental concerns were largely unimportant. The impact of information provision on GMF acceptance proved positive, suggesting information and education to be the main channels of creating public acceptance. The intrinsic interest regarding information related to GMF had an adverse impact on the perception of GMF morality. The benefits of the GMF proved unrelated to the GMF acceptance, indicating the gap in the information campaign. The research provides valuable insights for policymakers, public health professionals, and market researchers to communicate the GMF agenda effectively to the general public.